2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6697182
|View full text |Cite
|
Sign up to set email alerts
|

Explicit knowledge and the deliberative layer: Lessons learned

Abstract: Over the last four years, we have been slowly ramping up explicit knowledge representation and manipulation in the deliberative and executive layers of our robots. Ranging from situation assessment to symbolic task planning, from verbal interaction to event-driven execution control, we have built up a knowledge-oriented architecture which is now used on a daily basis on our robots.This article presents our design choices, the articulations between the diverse deliberative components of the robot, and the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Our approach has been informed by our experience with the BDI model of agency [5] and several associated agent architectures -architectures that were introduced to support a balance of deliberative and reactive behaviours, and that in their instantiation are reliant on domain-specific expert knowledge acquisition to provide a knowledge level view [6], c.f. [7], [8]. We are also supporters of the position that logicbased techniques are well suited to represent social reasoning and through which to engineer effective mechanisms, c.f.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach has been informed by our experience with the BDI model of agency [5] and several associated agent architectures -architectures that were introduced to support a balance of deliberative and reactive behaviours, and that in their instantiation are reliant on domain-specific expert knowledge acquisition to provide a knowledge level view [6], c.f. [7], [8]. We are also supporters of the position that logicbased techniques are well suited to represent social reasoning and through which to engineer effective mechanisms, c.f.…”
Section: Research Contextmentioning
confidence: 99%
“…Even though our focus is on cognitive mechanisms as essential components of an integrated cognitive architecture for effective social robots, and we have some exploratory work on human communication patterns [39], we recognise there are many topics important in such architectures that we do not attempt to address -spatial reasoning [40], dialogue actions [7], multimodal inputs [41], action signalling [24], the link between perception and action [42], [43], and comparisons between logic-based reasoning and other approaches such as game theory [44] and probabilistic reasoning [45] ... to name but a few! !…”
Section: Final Remarksmentioning
confidence: 99%
“…In fact, Niemueller et al [23] have shown that it is feasible to apply a document-oriented database like MongoDB, even for logging raw sensor data and analyzing robots' behavior in retrospect. Also knowledge-enabled and ontologybased approaches such as KnowRob [5], Robo Brain [6] or the OpenRobot Ontology (ORO) [7] rely on knowledge bases to store and query specifications of robots, their capabilities, tasks and environments. For the matter, this is complementary to the graph databases which we propose in this paper.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…This involves a) persistently storing the different notations and formats of DSLs; b) composing the various domain models; and c) querying over multiple domains at run time. The AI community has already realized this requirement, as evidenced by knowledge-enabled approaches like KnowRob [5], RoboBrain [6] or the OpenRobot Ontology (ORO) [7]. At the core of these approaches, graph-based knowledge representations such as ontologies provide common representations and query interfaces to the robot's runtime environment.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of plan synthesis and continuous plan execution has been demonstrated both for timeline based planning (e.g., [21]) and PDDL based (e.g., [22]). In scenarios of human robot interaction important problems have been addressed: (a) ''human aware'' planning has been explored for example in [23], (b) the interaction of background knowledge for robotic planning in rich domain (addressed for example in [24], (c) synthesis of safety critical plans to guarantee against harmful states (relevant in co-presence with humans) is addressed in [25] and [26]). Within the FourByThree project, a timeline-based planning approach is pursued relying on the APSI-TRF [27], developed for the European Space Agency and exploited in several missions.…”
Section: F Dynamic Task Planningmentioning
confidence: 99%